THE ROLE OF SCHOOL GEOGRAPHY EDUCATION IN THE INTEREST OF STUDENTS IN THE PROFESSION OF A GEOLOGIST (Scientific journal of the Fergana State University, 2024)
In our country, today tremendous work is being carried out to further develop the field of Geology and occupy a worthy place in the world community. As a result, the scope of the search work of minerals is expanding and new reserves are being identified. Large enterprises are being built on them, promising projects are being developed. Of course, qualified personnel are also needed for this. The development of the field of geology is carried out primarily by mature specialists of this field. The first steps for training and vocational guidance in this area can be done through school geography classes. Through school geography classes, students are also given early geological insights in conjunction with geographic knowledge. Through these classes, students gain initial perceptions of the field, knowledge, and skills. This article analyzes the possibilities of school geography education in the interest of students in the profession of a geologist and in the future in the direction of this profession.